Defense and Technical Cooperation Between Indonesia and Russia for the Defense and Security (2010-2015) - Ramadhan, Muhammad Iqbal; Maulina, Rizka (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
The rise of conflicts and crimes that threaten the sovereignty of the Republic of Indonesia is increasingly disturbing the defense and security of Indonesia. The weakening of the strength of the Indonesian National Army after the military embargo by the United States, France, and Germany made Indonesia feel the need to conduct military cooperation with other countries to improve the defense equipment and the quality of the Indonesian National Army as a means of National Defense. Russia, which is increasingly advancing in technology and military fields, has always sought the attention and support of developing countries in re-realizing its